[American workers from the most ubiquitous hazard present in today's modern workplace SEIU represents nearly one million workers in the United States and Canada The majority of our members work in public and commercial buildings many exposed daily] (Tufts Archival Research Center, 2007)
Marginalia; Letter from the SEIU to OSHA giving them the information they requested on indoor air quality. Describes the problems associated with poor indoor air, including lost work due to poor health. Contains an outline for OSHA with the best way to address the issue.